Dynamic soft tissue changes in the orbit after a blowout fracture. (2nd November 2019) - Felding, Ulrik Ascanius; Damgaard, Olaf E.; Bloch, Sune L.; Darvann, Tron A.; Thomsen, Carsten; Toft, Peter B.; von Buchwald, Christian
Abstract: Background/objectives: The intraorbital contents are thought to be affected by oedema in the days following a blowout fracture. We posit that this oedema can be detected by Magnetic resonance imaging (MRI) as changes in muscle volume, in muscle cross-sectional area, and in the MRI parameter 'mean grey value' (MGV) of the orbital fat and extraocular muscles (EOMs). Materials and methods: Patients with a blowout fracture underwent an MRI scan within 72 h after the trauma and again after 10–14 days. Measurements of EOMS and fat tissue on the fractured orbit were compared to the unfractured orbit. Results: Eighteen patients were included. Measurements showed significantly larger volume, cross-sectional area and MGV of the EOM closest to the fracture compared to the same muscle in the unfractured orbit. This significance disappeared for some parameters on the second scan. The volume of herniated orbital contents was significantly smaller on the second scan than on the first. Conclusions and significance: Based on the first longitudinal MRI study on patients with blowout fractures, our results indicate post-traumatic oedema in the intraorbital soft tissue which subsides between scans. A watchful waiting period is recommended in the initial post-traumatic days in patients without muscle entrapment.